X-cigale: fitting AGN/galaxy SEDs from X-ray to infrared. Issue 1 (24th October 2019) - Yang(杨光), G; Boquien, M; Buat, V; Burgarella, D; Ciesla, L; Duras, F; Stalevski, M; Brandt, W N; Papovich, C
ABSTRACT: Code Investigating GALaxy Emission (cigale ) is a powerful multiwavelength spectral energy distribution (SED) fitting code for extragalactic studies. However, the current version of cigale is not able to fit X-ray data, which often provide unique insights into active galactic nucleus (AGN) intrinsic power. We develop a new X-ray module for cigale, allowing it to fit SEDs from the X-ray to infrared (IR). We also improve the AGN fitting of cigale from UV-to-IR wavelengths. We implement a modern clumpy two-phase torus model, skirtor . To account for moderately extincted type 1 AGNs, we implement polar-dust extinction. We publicly release the source code (named 'x-cigale '). We test x-cigale with X-ray detected AGNs in SDSS, COSMOS, and AKARI-NEP. The fitting quality (as indicated by reduced χ 2 ) is good in general, indicating that x-cigale is capable of modelling the observed SED from X-ray to IR. We discuss constrainability and degeneracy of model parameters in the fitting of AKARI-NEP, for which excellent mid-IR photometric coverage is available. We also test fitting a sample of AKARI-NEP galaxies for which only X-ray upper limits are available from Chandra observations, and find that the upper limit can effectively constrain the AGN SED contribution for some systems. Finally, using x-cigale, we assess the ability of Athena to constrain the AGN activity in future extragalactic studies.